Resident perceptions on cross-cultural understanding as an outcome of volunteer tourism programs: the Bahamian Family Island perspective. Issue 9 (2nd September 2017) - Dillette, Alana K.; Douglas, Alecia C.; Martin, David S.; O'Neill, Martin
ABSTRACT: This paper examines the perceptions toward volunteer tourism from the viewpoint of Bahamian Family Island residents with a specific focus on cross-cultural understanding as an outcome. Cross-cultural understanding reflects the idea that there is a greater opportunity for exchange between tourists and residents as a result of volunteer tourism. Utilizing social exchange theory (SET), this research examines whether residents' perceived benefits, positive impacts, negative impacts and support for volunteer tourism activities predict their support for cross-cultural understanding. Additionally, this study reveals factors contributing to residents' motivation to participate in volunteer tourism activities within their community. A mixed-method research design that employed face-to-face interviews and quantitative surveys revealed eight major themes: Community Involvement, Empowerment, Sustainability, Education, Dependency, Neglect of Community Needs, Community Involvement and Communication. Multiple regression analysis results suggest partial support for SET and reveal new predictions for the support for cross-cultural understanding. Implications for volunteer tourism programs, host communities and national tourism organizations are discussed. Future research evaluating the volunteer–host relationship is warranted.